الطاقة الشمسية والغاز الصخري: خيارات الجزائر ما بعد النفط - بحري، دلال; عقابي، خميسة (جامعة باتنة 1 الحاج لخضر - كلية الحقوق والعلوم السياسية, 2018)
To keep up with the changes occurring in the international energy markets, Algeria has begun to adopt an energy strategy relying on solar energy regarding its enormous available potential, and in response to the requirements of sustainable development and environment conservation. On the other hand, Algeria’s orientation to shale gas exploitation, which requires a high technology development to be extracted and produced, with the obligation of setting laws that guarantee private environmental safety. We aim in this search article to show the potentials of Algeria in matter of solar energy and shale gas, and the necessity of their exploitation in the post-oil era, with the need to take advantage of the American experience, improve business climate, attract foreign investment and overcome obstacles.
لمواكبة التغيرات الحاصلة في أسواق الطاقة الدولية شرعت الجزائر في تبني استراتيجية طاقوية بالاعتماد على الطاقة الشمسية نظرا للإمكانيات الهائلة التي تتوفر عليها وكاستجابة لمتطلبات التنمية المستدامة والحفاظ على البيئة. ومن جهة أخرى توجه الجزائر نحو استغلال الغاز الصخري الذي يحتم عليها تطوير تكنولوجيا استخراجه وإنتاجه مع إلزامية سن قوانين صارمة تضمن السلامة البيئية خاصة. نهدف من خلال هذه الورقة البحثية إلى إظهار إمكانيات الجزائر من الطاقة الشمسية والغاز الصخري، وضرورة استغلالهما في مرحلة ما بعد النفط مع الحاجة إلى الاستفادة من التجربة الأمريكية وتحسين مناخ العمل وجذب الاستثمارات الأجنبية وتذليل العقبات.
Keywords: الطاقات المتجددة -- التنمية المستدامة -- الاستثمارات الأجنبية -- الجزائر